The potential of an exam villa as a structural resource during prolonged exam preparation at university - Reschke, Tom; Lobinger, Thomas; Reschke, Katharina (Frontiers in Education, 2023)
Drawing on the Demand-Control Model, this study examined whether using an exam villa as a supportive learning environment provides a structural resource for law students during exam preparation. First, we hypothesized that villa students show higher decision latitude and satisfaction and less stress compared to non-villa students. Second, we expected villa use to predict stress and satisfaction over and beyond the demand-control dimensions. Third, decision latitude was tested to mediate of the relationship between villa use and both outcomes. Our cross-sectional study included N = 205 advanced law students that gave self-reports on their stress and satisfaction, villa use, their perceived demands and decision latitude along with some control variables. All students were within a period of long-lasting exam preparation stretching over 12 to 18 months whereas n = 41 students used the villa. Using the exam villa was associated with both less subjective stress and more satisfaction. SEMs revealed villa use to predict stress but not satisfaction over and beyond the demand-control dimensions with 73% of overall explained variance in stress and 62% of variance in satisfaction. Decision latitude mediated the relationship between villa use and both outcomes. The findings support the potential of structural resources in reducing stress among students undergoing prolonged academic stress.